2019
DOI: 10.1007/s10534-019-00191-7
|View full text |Cite
|
Sign up to set email alerts
|

The indispensable role of mammalian iron sulfur proteins in function and regulation of multiple diverse metabolic pathways

Abstract: In recent years, iron sulfur (Fe–S) proteins have been identified as key players in mammalian metabolism, ranging from long-known roles in the respiratory complexes and the citric acid cycle, to more recently recognized roles in RNA and DNA metabolism. Fe–S cofactors have often been missed because of their intrinsic lability and oxygen sensitivity. More Fe–S proteins have now been identified owing to detection of their direct interactions with components of the Fe–S biogenesis machinery, and through use of inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 74 publications
(95 reference statements)
0
56
0
Order By: Relevance
“…Iron-sulfur (Fe-S) proteins play crucial roles in mammalian metabolism [166]. The study of the components of the Fe-S biogenesis machineries has led to the identification of a large number of proteins, whose importance for life is documented by an increasing number of diseases linked to these components and their biogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Iron-sulfur (Fe-S) proteins play crucial roles in mammalian metabolism [166]. The study of the components of the Fe-S biogenesis machineries has led to the identification of a large number of proteins, whose importance for life is documented by an increasing number of diseases linked to these components and their biogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…ABCB6 regulates porphyrin transport 15 . Our current knowledge on ABCB7 function remains presumptive 1114,16–26 . ABCB7 function in the heart is also not known.…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, there is a growing interest in the link among mitochondrial ABC transporters, iron metabolism, and cardiovascular diseases 24,1629 . The heart is a highly metabolically active organ which requires a continuous supply of ATP to sustain its contractile function.…”
Section: Introductionmentioning
confidence: 99%
“…To date, there are at least 18 known Fe/S cluster assembly proteins involved in proper biogenesis and trafficking of Fe/S containing clusters within mitochondria. A full review of this process is beyond the scope of this article but can be found elsewhere [229][230][231] .…”
Section: Iron-sulfur Cluster Biosynthesis and Mitochondrial Iron Homementioning
confidence: 99%